Arbuscular Mycorrhizal Fungi (AMF) diversity and population in UPV Nature Trail, Miagao, Iloilo, Philippines - EDGAR PHILIP T. DE ASIS; FRITZIE MARIE M. DEMETILLO; DIANA P. PAGUNTALAN (Society for Indonesian Biodiversity, 2023)
Abstract. De Asis EPT, Demetillo FMM, Paguntalan DP. 2023. Arbuscular Mycorrhizal Fungi (AMF) diversity and population in UPV Nature Trail, Miagao, Iloilo, Philippines. Biodiversitas 24: 6692-6703. Arbuscular Mycorrhizal Fungi (AMF) are soil microorganisms that form the most prevalent mutualistic associations with plant species. Studies revealed its global distribution in various terrestrial habitats, but available local literature remains few. This study investigated AMF diversity in the University of the Philippines Visayas (UPV) Nature Trail, Miagao, Iloilo, Philippines. AMF spores were isolated using wet sieving, decanting, and centrifugation. A total of 2815 individual spores were documented, with 114 distinct morphospecies representing 16 genera, nine families, and four orders classified. Glomus clarum, Acaulospora sp.7, and Scutellospora pellucida tallied the highest abundance across all points. Scutellospora pellucida (FOC=83.3%) recorded the highest species richness, followed by Ambispora sp. (FOC=77.78%), then Acaulospora mellea and Glomus australe (FOC=72.22%). Overall, Shannon-Weiner diversity index (H=3.6019) and Simpson diversity index (D=0.0420) revealed a very high AMF diversity in the trail, while the Pielou evenness index (J=0.7605) suggested a semi-balanced number of individuals among each morphospecies. A more abundant, even, and diverse, albeit not statistically significant, AMF community was recorded in forested areas compared to non-forested areas of the trail. Results generally suggest that the AMF community is diverse and abundant regardless of the location, ecosystem type, and faunal association.